2014
DOI: 10.1080/01431161.2014.978038
|View full text |Cite
|
Sign up to set email alerts
|

Parameter tuning in the support vector machine and random forest and their performances in cross- and same-year crop classification using TerraSAR-X

Abstract: This article describes the comparison of three different classification algorithms for mapping crops in Hokkaido, Japan, using TerraSAR-X data. In the study area, beans, beets, grasslands, maize, potatoes, and winter wheat were cultivated. Although classification maps are required for both management and estimation of agricultural disaster compensation, those techniques have yet to be established. Some supervised learning models may allow accurate classification. Therefore, comparisons among the classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…Random Forest classifications performed well, confirming the widely reported effectiveness of the RF algorithm for land cover classification (e.g., [15,58,64,65]), and particularly for mapping wetlands in tropical environments (e.g., [73,89,92]). Overall, OOB accuracy was above 80% for most models, above 90% for a selection of optimized models, and as high as 99% for model M1, which integrated spectral, SAR and topographic data, and images from multiple years and seasons.…”
Section: Random Forest Classifier Performance and Variable Importancesupporting
confidence: 61%
See 1 more Smart Citation
“…Random Forest classifications performed well, confirming the widely reported effectiveness of the RF algorithm for land cover classification (e.g., [15,58,64,65]), and particularly for mapping wetlands in tropical environments (e.g., [73,89,92]). Overall, OOB accuracy was above 80% for most models, above 90% for a selection of optimized models, and as high as 99% for model M1, which integrated spectral, SAR and topographic data, and images from multiple years and seasons.…”
Section: Random Forest Classifier Performance and Variable Importancesupporting
confidence: 61%
“…RF was selected for this study because it generally outperforms conventional classifiers such as the Gaussian maximum likelihood classifier [61,62], while performing favorably, or equally well, to other non-parametric approaches; e.g., CART [63,64], Support Vector Machines [32,65,66], Artificial Neural Networks [67], and K-Nearest Neighbor [68]. It is a powerful non-linear and non-parametric classifier that allows for fusion and aggregation of high-dimensional data from various sources (e.g., optical, SAR, and topography [30,69,70]; SAR and topography [21,58,71]; and optical and topography [72][73][74]).…”
Section: Image Classificationmentioning
confidence: 99%
“…Comparable to the report, Bagan et al [2012] concluded that the suitable γ value was 0.1 -0.2. It should be noted, however, that very big γ value (64) was found valuable for classification [Sonobe et al, 2014]. Similar case also applies with kernel selection.…”
Section: Introductionmentioning
confidence: 99%
“…Several supervised classification techniques have been proposed, generally categorized into parametric (including likelihood-based techniques) or non-parametric approaches, as used in decision trees and neural networks. Recent literature, however, tend to focus on the latter, especially SVM and RF [Chabrier et al, 2012;Naidoo et al 2014;Sonobe et al, 2014;Clewley et al 2015]. Both approaches have known being consistently superior than conventional methods such as maximum likelihood classification or decision trees [Rodriguez-Galiano and Chica-Rivas, 2014;He et al, 2015;Low et al 2015].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation